Association between feeling threatened by a terrorist attack and subjective health: a web survey a week after the attacks of 22 March 2016 in Belgium. Issue 1 (1st January 2018) - Deschepper, Reginald; Six, Stefaan; Gidron, Yori; Depoorter, Anne-Marie; Vandekerckhove, Marie; Gheysens, Nancy; Van Overmeire, Roel; Bilsen, Johan
ABSTRACT: Background : The wave of terrorist attacks over the past years in Europe and other regions may cause problems such as anxiety and depressive symptoms. Some studies suggest that perceived threat might also trigger physical health problems. Objective : To investigate the association between feeling threatened and subjective health during the week following a terrorist attack. Method : Online survey with a self-selected sample in the Belgian population one week after the terrorist attacks in 2016. Participants were invited through the Belgian media to fill in a questionnaire in Dutch, French or English on a website. The main outcomes were the association between 'feeling threatened' and subjective health problems. Perceived threat was measured with the question 'During the week after the attacks … Did you feel threatened?' Subjective health was measured by using standardized scales (ACSA, PHQ-4, PHQ-15). Results : A total of 2620 respondents completed the questionnaire, of whom 69.8% were female, 27.7% lived and 43.1% worked in Brussels. Gender, age, place of living and working, media exposure, religiousness and religious affiliation were associated significantly with higher perceived threat. A total of 21% of the respondents felt much or very much threatened during the week after the attacks. They reported significantly higher levels of mental and physical health problems. The most frequently reported problems were anxiety and depressive symptoms. The health problems that differentiated most markedly between those with low and high levels of perceived threat were fainting spells, chest pain and shortness of breath. Conclusion : In a self-selected sample of respondents, 'feeling threatened' was strongly associated with lower level of wellbeing and higher levels of mental and physical health problems. The most prevalent health problems were mental health problems but the most pronounced differences between people with low versus high levels of perceived threat were physical health problems.